Size effect on the fracture strength of lithium hydride and its implications for engineering structures - Zhirong Yang; Sicai Zhang; Qiang Huang; Dan Kang; Junjie Sheng; Haitao Hu (Materials & Design)
Due to its high hydrogen content, lithium hydride (LiH) has notable potential for hydrogen storage and neutron shielding; however, its inherent brittleness and susceptibility to thermal stress induced cracking limit its use in demanding environments. This study investigates the fracture behavior and size effect of LiH ceramics, focusing on its application in multilayer structures. Through experiments based on the Weibull statistical analysis, this research characterizes the fracture strength distribution of LiH specimens across different sizes, revealing that size-related flaws play a more dominant role in fracture behavior. The findings show that larger specimens have higher fracture probabilities under the same load conditions. In combination with the microscopic morphology and fracture characteristic analysis, it is concluded that surface defects on the LiH specimens play a significant role in the scatter of fracture strength. Then, the size effect analysis was conducted on a typical multilayer lithium hydride structure, demonstrating the differences in damage probability caused by the size effect. It highlights the critical need to consider size effects in the design and reliability evaluation of multilayer LiH structures. The insights gained here contribute to a more robust understanding of LiH ceramics in engineering applications, particularly under thermal stress.